Intergenerational Effects of Compulsory Schooling Reform on Early Childhood Development in a Middle-Income Country - Yusuf Emre Akgündüz; Pelin Akyol; Abdurrahman B. Aydemir; Murat Demirci; Murat Güray Kirdar (Institute of Labor Economics (IZA), 2024)
This paper explores the intergenerational effects of the 1997 compulsory schooling reform in Turkey, which extended compulsory schooling from five to eight years, on the developmental outcomes of children aged 36 to 59 months. We draw upon data from the 2018 Turkey Demographic and Health Survey, which features a comprehensive module on early childhood development (ECD), and estimate the impact of mothers' exposure to education reform using RDD. Our analysis reveals a significant increase in maternal educational attainment and corresponding enhancements in children's readiness to learn. Exploring the underlying mechanisms, we find a notable expansion in the number and variety of activities parents, especially fathers, engage in with their children. In a further examination of parental outcomes, we find evidence pointing to narrower educational and age disparities between partners, suggesting an improvement in mothers' agency—aligned with the heightened engagement of fathers with their children. Despite the typical emphasis on mothers in ECD research, our study indicates a significant enhancement in fathers' involvement with their children accompanied by improvement in children's cognitive outcomes.
Keywords: H52; I26; J13; J24; 330; compulsory education; early child development; parental investment; mother's agency; cognitive skills